2018
DOI: 10.3390/genes9050259
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and Occult Hepatitis B Virus Infection in Pregnant Women in Botswana

Abstract: The hepatitis B virus (HBV) is a global problem; however, the burden of HBV infection in pregnant women in Botswana is unknown. We sought to determine the prevalence of chronic and occult HBV infection in human immunodeficiency virus (HIV)-infected and -uninfected pregnant women in Botswana. Samples from 752 pregnant women were tested for hepatitis B surface antigen (HBsAg), and HBsAg-positive samples were tested for hepatitis B e antigen (HBeAg) and HBV DNA load. Samples that were HBsAg negative were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 43 publications
6
47
2
Order By: Relevance
“…Most HAART regimens in Botswana contain either tenofovir (TDF), lamivudine (3TC), or emtricitabine (FTC). These antiretrovirals have anti-HBV properties and could have resulted in the lower HBV prevalence in our cohort (5). A study by Anderson et al showed that there were 38% HB-sAg losses 24 months of post-Truvada-based cART initiation (17).…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Most HAART regimens in Botswana contain either tenofovir (TDF), lamivudine (3TC), or emtricitabine (FTC). These antiretrovirals have anti-HBV properties and could have resulted in the lower HBV prevalence in our cohort (5). A study by Anderson et al showed that there were 38% HB-sAg losses 24 months of post-Truvada-based cART initiation (17).…”
mentioning
confidence: 83%
“…Occult HBV infection is defined as having negative HBsAg but positive HBV DNA. We previously reported a 6.6% prevalence of occult HBV in pregnant women in Botswana (5).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations